SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN JAMKESDA MENGGUNAKAN METODE WASPAS - Sitompul, Joni Awendri; Munthe, Ibnu Rasyid; Sihombing, Volvo (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Jamkesda is a program that is more focused on the poor with the same service coverage as BPJS PBI (Penerima Bantuan Iuran). This program managed by the local government reaches poor people who are not registered with BPJS or Jamkesmas or who need additional health support at the regional level. One of the main challenges in implementing Jamkesda is determining who is entitled to receive benefits from this program, the recipient selection process must be based on clear and objective criteria, such as income, occupation, age, health conditions, and ownership of a Certificate of Inability to Pay (SKTM). To overcome this, a decision support system is used to facilitate the objective assessment process, namely the Weighted Aggregated Sum Product Assessment (WASPAS). This study obtained a final matrix result that was more significant than other alternatives with a value of 0.65498> 0.57926 which indicates A001> from A007 and is more significant than other alternatives.